Funciones desempeñadas como asistente administrativa en la empresa CONSTRUCTORA SHOPIA S.A.C. de la ciudad de Huamachuco (período 2012 - 2018) - Rios Araujo, Jessenia Nataly (2018)
The present Work of Professional Sufficiency entitled "Functions performed as administrative assistant in the company CONSTRUCTORA SHOPIA S.A.C. of the city of Huamachuco (period 2012 - 2018) ", has as objective to determine an adequate administrative management model for the company CONSTRUCTORA SHOPIA SAC, it was found the following main problem that has in the company is the lack of procedures for the elaboration of tenders with the state. To solve this problem, a process management model was proposed. Administration knowledge and process hierarchy were applied. A process redesign was applied; with the new process management model, the administrative processes were improved with the reduction of time in the preparation of offers up to the moment in which it is uploaded and presented to the public works portal; besides improving all other administrative aspects such as personnel management; the implementation of functions manual; the presentation and execution of public works among others; in itself it can be said that the administrative impact of the project was at a high level and improved the administrative quality of the company CONSTRUCTORA SHOPIA SAC, with the current process the company significantly improves its profitability, optimizing resources and budget for the preparation of a technical file, win the good pro, the execution of the work and the delivery of the same in the established times and fulfilling the assigned budget.